Equilibrium Effects of Pay Transparency - Cullen, Zoë B.; Pakzad-Hurson, Bobak (Econometrica, 2023)
The discourse around pay transparency has focused on partial equilibrium effects: how workers rectify pay inequities through informed renegotiation. We investigate how employers respond in equilibrium. We study a model of bargaining under two‐sided incomplete information. Our model predicts that transparency reduces the individual bargaining power of workers, leading to lower average wages. A key insight is that employers credibly refuse to pay high wages to any one worker to avoid costly renegotiations with others. When workers have low individual bargaining power, pay transparency has a muted effect. We test our model with an event‐study analysis of U.S. state‐level laws protecting the right of private sector workers to communicate salary information with their coworkers. Consistent with our theoretical predictions, transparency laws empirically lead wages to decline by approximately 2%, and wage declines are smallest in magnitude when workers have low individual bargaining power.